Service Quality, Drinking Water Quality, Food Quality and Corporate Performance: The Mediating Role of Supply Chain Management - Thaib, Danial; Hakimah, Yusro (ExcelingTech, 2020)
The study analyzes the mediating impact of supply chain management (SCMG) on the relationship among service quality (SRQL), drinking water quality (DRQL), food quality (FDQL) and corporate performance (CRPR). The target respondents of this research work were employees of water and food supply corporations situated in Thailand. The focused participants for the survey were the main managing directors, executives, CEOs and other high-positioning officials responsible for supply network exercises in firms. 75 firms were casually selected for the collection of data. After the information assortment, only 137 affirmed review structures were settled for examination. Path analysis using PLS-SEM is conducted to analyze the impact. CRPR and SCMG are used as dependent and mediating variables, respectively. SRQL, DRQL and FDQL are used as independent variables. The results of the study show that SRQL, DRQL and FDQL have significant positive impact on CRPR and SCMG. SCMG also has positive impact on CRPR. Moreover, the study also finds that SCMG mediates the association between SRQL and CRPR. It signifies that SRQL and SCMG together cause 21.7% changes in CRPR. SCMG also fully mediates the positive link between DRQL and CRPR. It reports that DRQL and SCMG collectively cause to change in CRPR by 9.4%. Moreover, SCMG also fully mediates the linkage between FDQL and CRPR as both SCMG and FDQL cause 13.2% variation in CRPR. From the findings, the study summarizes that better SCMG rises the services, food and drinking water quality of services, water and food supply corporations of Thailand which ultimately improves the corporate performance.